IMPLEMENTASI MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS AKSARA BALI DI PANTI ASUHAN YAYASAN DANA PUNIA SINGARAJA - A. A. Pt. Suari; Made Suardika Jaya; Komang Puteri Yadnya Diari; I Nengah Juliawan; I Ketut Suparya; I Putu Suardipa; I Nyoman Ariyoga (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service project was conducted to enhance the reading and writing skills of Balinese script among students at Yayasan Dana Punia Singaraja, who have limited access to structured and interactive learning resources. The Teams Games Tournament (TGT) model was selected for its ability to integrate collaborative learning with academic competition, thereby increasing learners’ engagement and motivation. The program consisted of several stages, including initial needs assessment, pre-test administration, implementation of the TGT model supported by digital learning media, guided practice sessions, and a post-test evaluation. The results indicate a notable improvement in participants’ ability to recognize, read, and write Balinese script, as reflected in the increased scores between the pre-test and post-test, alongside positive responses to the game-based learning activities. These findings demonstrate that the TGT model is effective for Balinese script instruction, particularly within heterogeneous learning groups. This program provides a valuable reference for educators and social institutions seeking to develop more adaptive, engaging, and sustainable learning strategies for the preservation and revitalization of Balinese script.